2021
DOI: 10.1002/cjp2.238
|View full text |Cite
|
Sign up to set email alerts
|

PRR11 unveiled as a top candidate biomarker within the RBM3‐regulated transcriptome in pancreatic cancer

Abstract: The outlook for patients with pancreatic cancer remains dismal. Treatment options are limited and chemotherapy remains standard of care, leading to only modest survival benefits. Hence, there is a great need to further explore the mechanistic basis for the intrinsic therapeutic resistance of this disease, and to identify novel predictive biomarkers. RNA-binding motif protein 3 (RBM3) has emerged as a promising biomarker of disease severity and chemotherapy response in several types of cancer, including pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…This is consistent with the previously reported role of PRR11 in non-small cell lung carcinoma [35,37]. Furthermore, PRR11 has been associated with other types of lung cancer [38], clear cell renal cell carcinoma [39], tongue squamous cell carcinoma [40], pancreatic cancer [41], gastric cancer [42], osteosarcoma [43], breast cancer [44], etc. It possibly exerts effects on the cell cycle and autophagy, eventually leading to tumorigenesis, progression, and poor prognosis of patients.…”
Section: Plos Onesupporting
confidence: 91%
“…This is consistent with the previously reported role of PRR11 in non-small cell lung carcinoma [35,37]. Furthermore, PRR11 has been associated with other types of lung cancer [38], clear cell renal cell carcinoma [39], tongue squamous cell carcinoma [40], pancreatic cancer [41], gastric cancer [42], osteosarcoma [43], breast cancer [44], etc. It possibly exerts effects on the cell cycle and autophagy, eventually leading to tumorigenesis, progression, and poor prognosis of patients.…”
Section: Plos Onesupporting
confidence: 91%
“…However, some studies have shown that overexpression of RBM3 is usually closely related to good clinical prognosis, and even used as a biomarker to evaluate cancer treatment (Al‐Astal et al, 2016). Deletion of RBM3 is associated with a variety of clinically more invasive cancers, and it is an independent factor of poor prognosis (Olsson Hau et al, 2022). High levels of RBM3 in prostate and breast cancer are a good biomarker of a low risk of cancer progression, low recurrence, and optimistic prognosis (Chen, Ikeda, et al, 2019).…”
Section: Rbm3 and Cancermentioning
confidence: 99%
“…The PRR11 gene on chromosome 17q22 encodes a proline-rich protein with a zinc finger domain and a bivalent nuclear localization signal 20 . Since its discovery in 2013, the relationship between this gene and tumors has been getting closer, and reports have revealed that it is related to the poor outcomes of various tumor types 21 , such as ovarian carcinoma 22 , breast cancer 23 , non-small cell lung cancer 24 , colorectal cancer 25 , and pancreatic cancer 26 . In addition, data indicate that it is involved in the epithelial-mesenchymal transition (EMT) process 27 .…”
Section: Introductionmentioning
confidence: 99%